Developing and assessing MyTBCompanion – A tri-lingual integrated video observed therapy app for tuberculosis patient management in Malaysia and Indonesia - Vimala Balakrishnan; Thayananth Kumaresan; Henry Surendra; Matthew Allsop; Chiong Kian Tiong; Nicholas Ng Jian Sheng; Mazlina Mohtar (PLoS ONE, 2025)
Background Limited studies have developed a mobile phone-based application that supports Asynchronous Video Observed Therapy (A-VOT) for Tuberculosis (TB) program. This study aimed to design, develop, and assess MyTBCompanion, a mobile phone-based digital health intervention to support A-VOT for TB management and care among low-income patients in Malaysia and Indonesia. Methods MyTBCompanion was designed and developed under a partnership involving experts in information technology, respiratory disease, and linguistics. Pre and Post-test surveys were done to assess feedback on the existing TB strategies (Direct Observed Therapy (DOT) and/or VOT) and the usability of the tested A-VOT strategy using MyTBCompanion. We collected data on the patient’s age, education level, current treatment strategy, and statements measuring four MyTBCompanion components: Engagement (how interesting, customizable, interactive and well-targeted to an audience an app is), Functionality (ease of use, app design, navigation), Aesthetic (the graphic design, overall visual appeal, color scheme, and stylistic consistency) and Information (content accuracy and relevance). The Mann-Whitney U test was performed for group comparisons, with results considered significant at p < 0.05. Results In total, 49 patients with TB were recruited from Malaysia (n = 29) and Indonesia (n = 20). Most participants in both countries were 20–40 years old. Indonesian participants mainly had tertiary education (11/20, 55.0%), whereas most had secondary education level in Malaysia (17/29, 58.6%). Most Malaysian participants (19/29, 65.5%) were using VOT through WhatsApp, with fewer (10/29, 34.5%) using DOT. All participants from Indonesia (20/20, 100%) were using the DOT strategy. Overall, compared to the existing strategies, a higher mean agreement score was observed for MyTBCompanion, with Information scoring the highest agreement (4.57/5.0), followed by Engagement (4.53/5.0), Functionality (4.51/5.0) and Aesthetic (4.49/5.0). Conclusion Findings suggest an overall good agreement on the usability of A-VOT strategy using MyTBCompanion in terms of engagement, functionality, information and aesthetics, with many indicating their willingness to recommend it to others, marking an encouraging milestone in the app’s development.